Linear Regression Analysis on Fluid Flow Rate in Tank Level Control - Rahayu, Puji; Ronald Sukwadi; Yahya, Agung Kurnia; Nurmalasari, Enny; Aini, Apsari Puspita (Journal of Chemical Process Engineering, 2024)
This research was conducted to study the effect of pump speed on changes in fluid levels in the tank and linear regression analysis of fluid flow. The variation used is a 4 mm solenoid and a variable pump speed range of 30-50%. The results of increasing the level at a pump speed of 32% obtained a level of 82 mm and a pump speed of 50% obtained a level of 149.9 mm, with fluid flow rotation occurring in the first minute. In addition, the determination calculation uses actual fluid level data at time 0 seconds (n=1), time 60.27 seconds (n=30), and time 180 seconds (n=61), with a fluid level value of 1 mm, 118 mm, and 141 mm. So the determination evaluation (R2) obtained is 0.863, which indicates that the model is included in the high tolerance category.  So this indicates that the PID controller in this series of piping system equipment is still suitable for use because in the recording of the fluid flow data obtained no significant gaps were found. Apart from that, it can also be seen that the pump speed affects the fluid flow rate due to the change in mechanical energy into kinetic energy which pushes the fluid towards the tank. Process time also influences changes in fluid levels in the tank as a result.